2012
DOI: 10.1002/ajhb.22271
|View full text |Cite
|
Sign up to set email alerts
|

Does celiac disease occur in Afro‐derived Brazilian populations?

Abstract: Our data suggests a low prevalence of celiac disease in African-derived Brazilian populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Of the five patients with definite CD, four were African and one was Indian; median age (IQR) was 24 years; and median body mass index 27.3 kg/m 2 . All the patients were asymptomatic.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the five patients with definite CD, four were African and one was Indian; median age (IQR) was 24 years; and median body mass index 27.3 kg/m 2 . All the patients were asymptomatic.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of ethnicity on CD prevalence remains unclear, but weak evidence has suggested that CD is rare in African origin populations . A Brazilian study that screened 10 Afro‐derived communities in the general population found that all 860 individuals tested negative for EMA, supporting a low prevalence of CD .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pernambuco (28) 2012 8 11.7 North east (African origins) (2) 2012 0 0 Mangueirinha (Kaingang & Guarani) (43) 2010 0 0…”
Section: Uk and Irelandmentioning
confidence: 99%